Assessment of nutrition status of Turkish elite young male soccer players in the pre-competition period
Background: Follow up of the nutrition consumption of young soccer players is of great importance not only for their sport performance, but also for the protection of health, physical growth and development. Aim: The objective of this study was to evaluate the nutritional sufficiency status of elite young male athletes in the pre-competition period. Methods: Three-day food consumption and anthropometric measurements of the elite young athletes in the pre-competition period were recorded for 26 male voluntary athletes from a pro-professional soccer team based in Ankara Turkey. Results: The mean height of the athletes were calculated as 175.2Å